Comprehensive Effect of the Time and Water-Cement Ratio on the Rheological Properties of Power-Law Cement Grouts. (14th August 2021) - Zhi-quan, Yang; Yi, Ding; Ya-peng, Mi; Ying-yan, Zhu; Yi, Yang; Yan-hui, Guo; Bi-hua, Zhang; Shi-hou, Li; Jian-kun, Su; Jun-zhi, Chen; Wan-zhong, Xu; Wan-lin, Liu; et al.
Abstract : The rheological properties of cement grouts are significantly affected by the changes of the time and the water-cement ratio, which determine the diffusion state of grouts in rocks and soils and influence the outcome of projects. In this study, Portland cement grouts with water-cement ratios of 0.50, 0.55, 0.60, 0.65, 0.70, and 0.75 at six moments, including 0 minutes, 5 minutes, 10 minutes, 20 minutes, 30 minutes, and 60 minutes, were evaluated to figure out the comprehensive effect of the time and the water-cement ratio on the rheological properties of power-law cement grouts. The results showed that the water-cement ratio had a great influence on both the consistency coefficient and the rheological index of the power-law cement grouts. The former appeared to have a downward trend with the increase of the water-cement ratio, and the latter appeared to have an upward trend. There was a rising tendency between the time and the consistency coefficient, while the rheological index was less affected by time. The difference between its maximum and minimum values was within 5%. Combined with the perspectives of statistical theory, practical applicability, and accuracy, the exponential model was the optimal model for showing the relationship between the comprehensive effects of the time, water-cement ratio, and consistency coefficient of the power-law cement grouts. The linear model was the optimal model of the rheological index based on the comprehensive effect of time and the water-cement ratio. Based on this, a power-law rheological equation with consideration of the comprehensive effect of time and water-cement ratio was established. The research results could not only improve the rheological theory of power-law cement grouts but also provide technical support for engineering practice.